The spectrum of HNF1A gene mutations in patients with MODY 3 phenotype and identification of three novel germline mutations in Turkish Population. (November 2017) - Karaca, Emin; Onay, Huseyin; Cetinkalp, Sevki; Aykut, Ayca; Göksen, Damla; Ozen, Samim; Atik, Tahir; Darcan, Sukran; Tekin, Ismihan Merve; Ozkınay, Ferda
Abstract: Background: Maturity-onset diabetes of the young (MODY) is a monogenic form of diabetes mellitus characterized by autosomal dominant inheritance, early age of onset, and pancreatic beta cell dysfunction. Heterozygous mutations in several genes may cause MODY. Methods: In the present study, we investigated the molecular spectrum of HNF1A (hepatocyte nuclear factor 1a) mutations, in the individuals referred to a reference center for molecular genetic analysis. Mutations screening was performed in a group of 136 unrelated patients (average age 17.22 years) selected by clinical characterization of MODY. Mutation screening involved direct sequencing of the HNF1A gene. Results: Among 136 individuals analyzed, 10 were carrying heterozygous HNF1A mutations, 3 of them being novel. Clinical features, such as age of diabetes at diagnosis or severity of hyperglycemia, were not related to the mutation type or location. No clear phenotype – genotype correlations were identiﬁed. Conclusions: As a conclusion MODY resulted from HNF1A mutations shows heterogeneity at both phenotypic and molecular levels in Turkish population.